The innovator's method : bringing the lean startup into your organization - Furr, Nathan R.
"A radical new method-adapting the latest techniques honed by successful start-ups-for managing innovation in established businesses. Call it "lean start-up," "design thinking," or "agile." No matter the name, it's clear that a new method is revolutionizing how to successfully create, refine, and bring ideas to market-without traditional business planning. But because these ideas and techniques run counter to conventional managerial thinking and practice, managers in established organizations have difficulty implementing them. No longer. Based on field work with thousands of managers and validated inside dozens of companies, innovation experts Nathan Furr and Jeff Dyer show when and how to apply a "lean start-up" approach to innovation in established businesses. The Innovator's Method takes managers through these new practices for managing innovation. With detailed cases from the authors' work implementing these ideas with companies such as Intuit, NEC, P&G, Virgin Airlines, Kia, Folio, Citi, Hallmark, and Verizon, The Innovator's Method picks up where Jeff Dyer's The Innovator's DNA leaves off, showing how to test, validate and commercialize ideas with the lean and agile techniques that successful entrepreneurs use"--